A clear path to endemic: An opportunity to increase healthcare professionals’ system - Subrata, Sumarno Adi; Sahin, Busra (Innovation in Health for Society, 2023)
The COVID-19 pandemic brought to light some of the most severe flaws in the healthcare system, but it also sparked a flurry of ideas resulting in a significantly enhanced delivery system. These were innovations that were brought about as a direct result of a pressing need: telenursing for community services; telemedicine access and use skyrocketed; new hospital-at-home services emerged; ambulatory surgical centres expanded their menu of procedures; and a variety of novel therapeutics were introduced, including the widespread distribution of vaccines, new medical diagnostics, and innovative monoclonal antibodies. A new era of digital medicine during the endemic may be on the horizon due to the proliferation of new services that feature adaptable delivery methods. Therefore, healthcare professionals need to improve the system, including reevaluating and redeveloping it for a better quality of care in clinical settings and community. Keywords: Quality care; COVID-19; telenursing; telemedicine; community services; innovation in health